BMI and healthy life expectancy in old and very old women. Issue 4 (16th June 2016) - Leigh, L.; Byles, J. E.; Jagger, C.
Abstract: There is conflicting evidence for the effect of BMI on mortality at older ages, and little information on its effect on healthy life expectancy (HLE). Longitudinal data were from the 1921–1926 cohort of the Australian Longitudinal Study on Women's Health ( n 11 119), over 18 years of follow-up. Self-rated health status was measured at each survey, and BMI was measured at baseline. Multi-state models were fitted to estimate the effect of BMI on total life expectancy (TLE) and HLE. Compared with women of normal weight, overweight women at the age of 75 years had similar TLE but fewer years healthy (−0·79; 95 % CI −1·21, −0·37) and more years unhealthy (0·99; 95 % CI 0·56, 1·42). Obese women at the age of 75 years lived fewer years in total than normal-weight women (−1·09; 95 % CI −1·77, −0·41), and had more unhealthy years (1·46; 95 % CI 0·97, 1·95 years). Underweight women had the lowest TLE and the fewest years of healthy life. Women should aim to enter old age at a normal weight and in good health, as the slight benefit on mortality of being overweight is offset by spending fewer years healthy. All outcomes were better for those who began in good health. The relationship between weight and HLE has important implications for nutrition for older people, particularly maintenance of lean body mass and prevention of obesity. The benefit of weight loss in obese older women remains unclear, but we support the recommendation that weight-loss advice be individualised, as any benefits may not outweigh the risks in healthy obese older adults.